Journal of Political Economy (Journal of Political Economy, 2017)
Next article FreeJournal of Political EconomyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Johannes AbelerRan AbramitzkyChristian AhlinMohammad AkbarpourFranklin AllenMary AmitiMichael AndersonJose ApesteguiaKentaro AsaiEnghin AtalayOrazio AttanasioEduardo AzevedoLinda BabcockAna BabusSandeep BaligaEmek BaskerMarco BassettoNathaniel Baum-SnowMark BilsPietro BiroliDaniel BjorkegrenHoyt BleakleyJaroslav BorovickaAbel BrodeurEric BudishMichael BurdaRobin BurgessLeonard BurmanLeonardo BursztynMichael CallenColin CamererJohn CampbellIvan CanayDavid CardJuan CarrilloGabriel CarrollAnne CaseTimothy CasonSylvain ChassangDean CorbaeThomas CovertThomas CrossleyFlavio CunhaManasi DeshpandeWouter DesseinChristian DippelMatthias DoepkeThomas DohmenMei DongLaura DovalJoseph DoyleLukasz DrozdGilles DurantonFederico EcheniqueJan EeckhoutPaul EllicksonJose-Antonio Espin-SanchezPablo FajgelbaumArmin FalkMaryam FarboodiRobert FeenstraErnst FehrAmy FinkelsteinUrs FischbacherRaymond FismanMarco FrancesconiXavier GabaixRoberto GalbiatiJordi GaliSebastian GalianiNicolae GarleanuMatthew GentryRobert GibbonsMichael GibbsYuriy GorodnichenkoGautam GowrisankaranAndrei HagiuMarina HalacYoram HalevyGlenn HarrisonTarek HassanTarjei HavnesOri HeffetzJ. HendersonNathaniel HendrenRichard HoldenMatthew JohnsonBoyan JovanovicJames KahnDean KarlanMaximilian KasyJun Hyung KimPatrick KlineRalph KoijenFabian KosseMatthew KotchenPer KrusellPablo KurlatRicardo LagosThomas LemieuxJacob LeshnoTong LiLance LochnerFernando LucoJeremy MagruderNeale MahoneyDavid MalisonVikram ManjunathRosa MatzkinBhashkar MazumderRobert McMillanAlbert MenkveldGuido MenzioIgnacia MercadalBruce MeyerAtif MianSanjog MisraGiuseppe MoscariniTakeshi MurookaCaitlin MyersSuresh NaiduDavid NeumarkNathan NunnBenjamin OlkenEmily OwensMichaela PagelAmanda PallaisFernando ParroJesse PerlaCharles PlottDevin PopeNancy QianSteven RaphaelMartin RavallionAlex Rees-JonesMatthew RichardsonJohn RobertsJames RobertsAndres Rodriguez-ClareLeena RudankoNicholas RyanStephen RyanTobias SalzCezar SantosMichael SattingerPeter SavelyevMoritz SchularickStephan SeilerAmit SeruAloysius SiowChristopher SnyderPaulo SomainiPer StrombergAdam SzeidlXun TangRaphael ThomadsenMallika ThomasAllan TimmermannPetra ToddAlexander TorgovitskyRobert TownUtku UnverRobert VallettaFrederic VermeulenAlessandra VoenaTill Von WachterQuang VuongRomain WacziargReed WalkerNeil WallaceMike WaughEric WeylPaul WillenBen WilliamsRegina Wittenberg-MoermanAlexander WolitzkyNese YildizNoam YuchtmanAli YurukogluJidong ZhouJonathan Zinman Next article DetailsFiguresReferencesCited by Journal of Political Economy Volume 125, Number 6December 2017 Article DOIhttps://doi.org/10.1086/696330 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.